2014
DOI: 10.3109/02770903.2014.952434
|View full text |Cite
|
Sign up to set email alerts
|

Trends in prevalence and risk factors of childhood asthma in Fuzhou, a city in Southeastern China

Abstract: The prevalence of asthma in childhood has increased significantly during the past 20 years in Fuzhou.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…Using a split AC system was a risk factor, possibly because cleaning these devices is difficult, which may lead to the accumulation of allergens and other substances. 26 In China, air conditioning systems are also significantly associated with asthma in schoolchildren, 27 although these systems may protect against traffic-related exposures at home, as reported in Singaporean children. 28 Finally, a high frequency of paracetamol intake was a risk factor for asthma in our study, which is in agreement with global ISAAC findings.…”
Section: Discussionmentioning
confidence: 99%
“…Using a split AC system was a risk factor, possibly because cleaning these devices is difficult, which may lead to the accumulation of allergens and other substances. 26 In China, air conditioning systems are also significantly associated with asthma in schoolchildren, 27 although these systems may protect against traffic-related exposures at home, as reported in Singaporean children. 28 Finally, a high frequency of paracetamol intake was a risk factor for asthma in our study, which is in agreement with global ISAAC findings.…”
Section: Discussionmentioning
confidence: 99%
“…Poor ventilation in indoor bedrooms is common, especially in deprived areas [ 28 ]. In some regions and because of the high temperature, windows and doors are open most of the time, and some studies revealed that in those settings natural ventilation is a protective factor for asthma [ 29 ]. The climate also predisposes to insect bites that induce papular urticaria.…”
Section: Introductionmentioning
confidence: 99%
“…The onset of asthma onset occurs before the age of 12 (years) in over half the cases. The past 20 years have seen a significant increase in the prevalence of asthma in children (Tang et al, 2015). The pathogenesis of asthma is related to multiple risk factors including environmental factors such as vehicular pollution, and genetic factors such as polymorphisms in the interleukin (IL)-4 and ORMDL3 genes (Favarato et al, 2014;Tang et al, 2014;Zhai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%